Energy-saving technologies and means of mechanization of a new generation for cultivation of soybean and cereals in the system of biological farming - A. V. Syumak (Аграрная наука Евро-Северо-Востока)
The researches were conducted on the heavy seasonally-frozen periodically overwet soils in conditions of the Amur region. The energy-saving agricultural technologies were tested on the basis of a complex of the new generation of machines (OVPP-2.5; MMU-3.6; BPRZ-1.2) in comparison with the basic technologies and technical means. The production testing of energy-saving technologies at cultivation of barley (variety Acha) and soybean (variety Lidya) was carried out in 3-field short crop rotation (green-manured fallow - barley -soybean). In accordance with these technologies three methods of soybean sowing were tested conducted by MMU-3.6, compared to an ordinary method with the use of serial seeding-machine SZ-3.6 with row spacing of 15 cm. In sowings conducted by MMU-3.6 the selected depth of seed placement was kept regardless of applied coulters (variations did not exceed ±0.67 cm). The researches confirmed that the uniformity of seed distribution on the area of the bands improves the yield compared to the row sowing. As a result of production testing of energy-saving technologies it was marked a significant increase in the yield of barley (1.4 times) and soybean (2.3 times). The highest soybean yields was achieved at using wide-band sowing method, width of band is 20 cm - 3.26 t/ha, and band-pass sowing method, width of band is 10 cm - 2.77 t/ha. The decrease in the amount of technological operations at cultivation of barley and soybean allowed to reduce fuel consumption by 1.3 and 1.5 times respectively in comparison with the basic technologies. The energy effect amounted to 1170.78 GJ at cultivation of barley and 2293.67 GJ at cultivation of soybean.